Strategi Keamanan Dalam Pencegahan Konflik Pertanahan Di Wilayah Hukum Polres Kota Tangerang (Studi Kasus Konflik Pertanahan antara Haji Sobari dan Merna Siriyanti) - Kanitero, David Yunior (Jurnal Kajian Stratejik Ketahanan Nasional, 2021)
This research was conducted to explore the phenomenon of security strategies in preventing land conflicts between two groups that face each other and have the potential to cause physical clashes in the jurisdiction of the Tangerang City Police. This land conflict between Haji Sobari and Merna Siriyanti actually appeared on the surface in 1997. At that time, the land located at Jalan Industri Raya IV Block A Kp. Bunder Rt. 12 RW. 03 Bunder Village, Cikupa District, Tangerang Regency, Banten was occupied by Haji Sobari and his family. However, the land is also claimed by Merna Siriyanti, who claims that the land is hers. In the time span from 1997 to the present, in 2016, the land conflict that originally only involved the individual versus the individual has turned into two groups that confront and destroy each other. In an effort to deal with land conflicts between Haji Sobari and Merna Siriyanti, in this case at the prevention stage, the Tangerang City Police seem to be working alone without coordinating with stakeholders, for example the Regional Government, BPN, or the Courts. The prevention efforts carried out by the Tangerang City Police in carrying out early detection, pre-emptive, and preventive functions are still not optimal. Keywords: security strategy, land conflicts, early detection, pre-emptive, preventive